SenseDependency-rank: A word sense disambiguation method based on random walks and dependency trees - Sobrevilla Cabezudo, M.A.; Oncevay, A.; Sasieta, A. (Springer Verlag, 2018)
Word Sense Disambiguation (WSD) is the field that seeks to determine the correct sense of a word in a given context. In this paper, we present a WSD method based on random walks over a dependency tree, whose nodes are word-senses from the WordNet. Besides, our method incorporates prior knowledge about the frequency of use of the word-senses. We observed that our results outperform several graph-based WSD methods in All-Word task of SensEval-2 and SensEval-3, including the baseline, where the nouns and verbs part-of-speech show the better improvement in their F-measure scores.
Keywords: Word Sense Disambiguation; Random walks; Dependency tree; https://purl.org/pe-repo/ocde/ford#1.02.02